2016
DOI: 10.1016/j.geotexmem.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and physical modeling of geofoam barriers as protection against effects of surface blast on underground tunnels

Abstract: a b s t r a c tAn explosion on the ground surface may cause significant damage to an underground structure, such as a tunnel or a pipeline. The extent of damage would depend on the intensity of blast, the material and configuration of the structure, as well as the nature and geometry of the intervening material.An underground structure may be protected by means of a protective barrier, installed directly above the structure. The effectiveness of using a compressible barrier, made of polyurethane geofoam, to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…It was recommended that, to create a blast resistant tunnel design, an increase in the lining thickness shall be a viable option. De et al [37] suggested the geofoam material to be placed directly above the structure to prevent it against blast load. It was observed that the measured stresses, strains and pressures at the top of the tunnel found decrease when the protective geofoam barrier's thickness was increased.…”
Section: Influence Of Lining Materials In Tunnelmentioning
confidence: 99%
“…It was recommended that, to create a blast resistant tunnel design, an increase in the lining thickness shall be a viable option. De et al [37] suggested the geofoam material to be placed directly above the structure to prevent it against blast load. It was observed that the measured stresses, strains and pressures at the top of the tunnel found decrease when the protective geofoam barrier's thickness was increased.…”
Section: Influence Of Lining Materials In Tunnelmentioning
confidence: 99%
“…6, when charge reached 300 kg the stress reached the tunnel is more than the ultimate compressive strength of concrete 50 MPa. At great charges a protection like layers of foam or RC slab should be created for the tunnel to reduce energy conveyed to it, [16,37].…”
Section: Effect Of Weight Of Tntmentioning
confidence: 99%
“…The destructive effects of blast loads have directed many investigators to study how the explosions affect the response of structures and the methods to dilute the risks using both tests and simulation models. The damage mode of tunnels in both dry and saturated soil were studied through experimental and numerical studies of blast loads [9][10][11][12][13][14][15]. The explosions tests are very limited due to their complexity and high cost.…”
mentioning
confidence: 99%
“…Using the artificial gravity field generated by a centrifuge, a large explosion can be simulated with fewer explosives [9]. erefore, scholars have established centrifuge models to evaluate how surface explosion affects underground structures [10]. Also, as the processing capability of computers has grown, numerical simulations have entered widespread use in this field.…”
Section: Introductionmentioning
confidence: 99%